Production Optimization Analysis Based on Effective Working Hour of Mobile Crusher Unit 02: Case Study in PT Mifa Bersaudara, West Aceh - Oziana, Deea Rizki; Syafitri Amanda; Nurul Aflah; Pocut Nurul Alam; Nurul Kamal (Jurnal Serambi Engineering, 2026)
PT Mifa Bersaudara is a coal mining company located in Meureubo, West Aceh, Indonesia. This study evaluates and optimizes the Effective Working Hours (EWH) of Mobile Crusher 02 (MC02), one of the key units in the coal crushing process. The primary constraint identified is the inability to achieve production targets due to excessive downtime, particularly standby time and equipment breakdowns, which significantly reduce operational efficiency. A quantitative descriptive approach was applied using primary field observations and secondary production data from May to June 2025. The analysis focused on downtime components, effective working hours, and equipment availability based on Mechanical Availability (MA), Physical Availability (PA), Utilization of Availability (UA), and Effective Utilization (EU). Results indicate that MC02 operated for an average of only 7 effective working hours out of 10.05 available hours, reflecting an efficiency level of 69.65%. Standby time accounted for the largest portion of downtime at 141.86 hours. Following the implementation of operational improvements aimed at reducing delays, overall efficiency increased, and production rose from 128,505 tons to 168,864 tons, achieving 112% of the targeted output. These findings demonstrate that improving EWH has a direct and significant impact on crusher productivity and provides a foundation for future operational optimization in the coal processing system.